THE DETERMINANTS OF PROFIT CHANGE IN MANUFACTURING COMPANIES AT THE INDONESIAN STOCK EXCHANGE - Nusbantoro, Ariwan Joko; Utami, Elok Sri; Sanjaya, Nori Alfiani (Review of Management and Entrepreneurship, 2019)
This study examines the determinants of profit change of companies in the manufacturing sector listed at the Indonesia Stock Exchange. The independent variables include working capital ratio, time interest earned ratio, gross profit ratio, and firm size. The data are extracted from the companies’ financial statements covering a period from 2012 to 2015. A total of 83 companies met the sample selection criteria. Results using multiple linear regression analysis show that working capital ratio and gross profit ratio both have significant negative effect on profit change, the ratio of interest payment has no positive effect on profit change, and firm size has no significant effect on profit change.